Climate Change Versus Global Warming: Who Is Susceptible to the Framing of Climate Change?. (August 2017) - Benjamin, Daniel; Por, Han-Hui; Budescu, David
The terms global warming and climate change are often used interchangeably, but recent research finds "global warming" has become more emotive and more polarizing, resulting in less advocacy by some subpopulations. We explore the robustness of this framing effect based on the expectation that people with stronger partisan identities tend to have more deep-seated climate change beliefs. We use multiple methods and measures to study framing across a range of attitude scales designed to measure climate change beliefs, degree of knowledge about climate change, and intentions to take corrective actions. We find stronger framing effects for political Independents and those who are disengaged from climate change issues, indicating that polarization overrides framing at the extremes, and those with moderate beliefs are more susceptible to labeling and framing effects, especially when beliefs are inconsistent with one's political identity. We conclude by urging communicators to appreciate the heterogeneity of their target audience.